Methodological basis of construction of the system of monitoring and stratification of universities - Rayevnyeva, Olena; Aksonova, Iryna; Brovko, Olha (BoScience Publisher, 2021)
The role of monitoring in the formation of information-analytical and methodological base of research of the market of educational services is shown. A methodical approach to building a system of monitoring and stratification of universities (SMSU) is proposed. The first stage of construction of the SMSU is considered, namely the methodological basis in the form of hypotheses, provisions, principles of functioning of the monitoring system.
Keywords: monitoring system; university stratification; higher education institution; hypothesis; monitoring principles